Shellac-based natural-source sun-screening agent, preparation method thereof and application of shellac-based natural-source sun-screening agent in sun-screening cosmetics

By combining modified shellac with fat-soluble sunscreen and emulsifier, shellac-based natural sunscreen is prepared, which solves the safety hazards of traditional sunscreens and the insufficient performance of inorganic shielding agents, and achieves efficient and safe sunscreen protection The effect has expanded the application of shellac in the field of sun protection.

CN119302872AActive Publication Date: 2025-01-14JIANGNAN UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411420161.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-14
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

Traditional organic small molecule sunscreens produce reactive oxygen free radicals under UV radiation, which poses safety risks and has a negative impact on marine ecosystems. Inorganic ultraviolet shielding agents damage skin cells under UV radiation and add too much to cause cosmetics to turn white It is thick and difficult to expand the application of shellac in the field of sun protection.

Method used

Combination of modified shellac, fat-soluble sunscreen agent and emulsifier, composite nanoparticles are prepared by anti-solvent precipitation method, significantly improving the ultraviolet absorption performance of shellac, and preparing shellac-based natural sunscreen agents for preparation with good results Sunscreen for sun protection.

Benefits of technology

It has improved the SPF value of sunscreen, significantly improved biocompatibility and ultraviolet absorption effect, expanded the application prospects of shellac in the sun protection field, and provided a safe and effective natural sun protection solution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119302872A_ABST
    Figure CN119302872A_ABST
Patent Text Reader

Abstract

The invention discloses a shellac-based natural-source sun-screening agent as well as a preparation method and application thereof in sun-screening cosmetics, and relates to the field of daily chemicals. The shellac-based natural-source sun-screening agent disclosed by the invention is a composite nanoparticle, and the composite nanoparticle is prepared from the following raw materials in parts by mass: 2 to 10 parts of modified shellac, 1 to 1.5 parts of fat-soluble sun-screening agent and 0.01 to 1 part of emulsifying agent. The preparation method comprises the following steps: dissolving the modified shellac in absolute ethyl alcohol at the concentration of 10-15mg / mL, centrifuging to remove impurities, dissolving the fat-soluble sun-screening agent in an ethanol solution of the modified shellac, cooling to room temperature, preparing composite nanoparticles by an anti-solvent precipitation method, dissolving the emulsifier in an anti-solvent, carrying out rotary evaporation to remove ethanol, and freeze-drying. The sunscreen cream prepared from the shellac-based natural-source sunscreen agent has good biocompatibility and sunscreen performance, can generate a compounding effect in a form of being blended with other sunscreen cream, and has a wide application prospect in the field of sunscreen cosmetics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a shellac-based natural source sunscreen agent and a preparation method thereof and application in sunscreen cosmetics, belonging to the field of polymer composite nano materials. Background Art

[0002] Ultraviolet (UV) is a type of electromagnetic radiation emitted by the sun. UV radiation can be divided into three wavelength ranges: UVA (315-400nm), UVB (280-315nm) and UVC (100-280nm). The destruction of the ozone layer causes strong ultraviolet light to directly irradiate the earth. UV has a higher frequency and therefore contains greater energy. When it directly irradiates the skin, UVA can directly penetrate the surface of the human skin and reach deep into the dermis, destroying human tissues and cells, causing muscles to lose elasticity, causing skin sagging, wrinkles, freckles and age spots; UVB can denature nucleic acids or proteins in cells on the surface of the skin, causing the skin to turn red, and even causing acute dermatitis and erythema (sunburn). Long-term and intense UV exposure can lead to skin cancer. There are about 500,000 new skin cancer patients in the United States each year, and research results show that more than 98% of these patients are cancer-causing due to sunlight factors. Therefore, organic or inorganic sunscreens with sunscreen functions are increasingly attracting attention.

[0003] Sunscreens used in cosmetics on the market are generally divided into organic small molecule UV absorbers and inorganic UV shielding agents. Inorganic UV shielding agents that have passed national safety certification in various countries mainly include titanium dioxide and zinc oxide, while the types and maximum addition limits of organic small molecule UV absorbers vary from country to country. However, traditional organic small molecule sunscreens are prone to produce reactive oxygen free radicals (ROS) under UV radiation, which in turn damage cells. According to a study by the U.S. Food and Drug Administration (FDA) in May 2019 (Effect of Sunscreen Application Under Maximal Use Conditions on Plasma Concentration of Sunscreen Active Ingredients, The Journal of the American Medical Association, 321), although the types and amounts of sunscreen ingredients in sunscreen products on the market are within the regulations, after volunteers used sunscreen products for one day, the levels of chemical components of four common sunscreens, including avobenzone, oxybenzone, octocrylene, and ecamsule, in their blood exceeded the prescribed level of 0.5 nanograms per milliliter, and with repeated use of sunscreen products, the concentrations of these chemical components in the blood continued to increase. It can be seen that traditional organic small molecule sunscreens still have great safety risks during human use, and also have a negative impact on marine ecosystems and water resources around the world. Inorganic UV shielding agents such as titanium dioxide will also produce reactive oxygen free radicals (ROS) that can damage skin cells under UV radiation, and the shielding effect on UV rays is not significant when the content is small, so it is necessary to increase the amount added and use it in combination with organic small molecule sunscreen agents. However, adding a large amount of inorganic UV shielding agents will cause sunscreen cosmetics to become white and heavy, making it difficult to apply and disperse the film, and consumers will have a poor experience.

[0004] Therefore, due to the safety, renewability and rich biological activity of natural compounds, more and more attention is focused on their sunscreen applications. Among them, shellac, as a food-grade amphiphilic natural polymer, has good biodegradability and biocompatibility, low cost, abundant sources and renewable, and has broad application prospects for the preparation of composite nano-sunscreen particles. However, the ultraviolet absorption effect of the shellac molecule itself is not significant, so it is necessary to explore a shellac-based natural source sunscreen with good ultraviolet absorption effect to expand its application in the field of sunscreen. Summary of the invention

[0005] In order to overcome the problem that the ultraviolet absorption effect of the shellac molecule itself is not significant, the present invention provides a shellac-based natural source sunscreen and its preparation method and application in sunscreen cosmetics. The sunscreen prepared by the present invention has good biocompatibility, ultraviolet absorption effect and compounding effect, and can effectively improve the SPF value of sunscreen cosmetics.

[0006] The specific content of the present invention is as follows:

[0007] A shellac-based natural sunscreen is a composite nanoparticle, comprising the following raw materials in parts by weight: 2 to 10 parts of modified shellac, 1 to 1.5 parts of a fat-soluble sunscreen, and 0.01 to 1 part of an emulsifier; the modified shellac is a dextran-grafted shellac product.

[0008] In one embodiment, the preparation method of the modified shellac is: completely dissolving the shellac in dimethyl sulfoxide (DMSO), adding 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) for activation at room temperature, and adding 4-dimethylaminopyridine (DMAP) and aminodextran (NH2-DEX) for amidation reaction.

[0009] In one embodiment, the preparation method of modified shellac comprises the following specific steps: completely dissolving the shellac in DMSO, then adding EDC for activation at room temperature, the activation time is 30 minutes, the activation temperature is 40°C, adding DMAP and NH2-DEX for amidation reaction, the reaction time is 16 to 24 hours, and the reaction temperature is 40°C.

[0010] In one embodiment, the fat-soluble sunscreen is one or a combination of sinapinic acid, catechin, resveratrol, quercetin, ferulic acid, octocrylene, ethylhexyl methoxycinnamate, ethylhexyl triazone, ethylhexyl salicylate, homosalate, and avobenzone.

[0011] In one embodiment, the emulsifier is any one of an anionic emulsifier and a nonionic emulsifier or a mixture of two;

[0012] In one embodiment, the emulsifier is at least one of sucrose ester 11, sodium lauryl sulfate, Tween 80, Span 80, Brij721, Brij72, Brij30, glyceryl stearate and sodium cetearyl sulfate.

[0013] In one embodiment, the concentration of the shellac dissolved in dimethyl sulfoxide is 15-30 mg / mL; the temperature when the shellac is dissolved in dimethyl sulfoxide is 30-50° C.; the stirring speed when the shellac is dissolved in dimethyl sulfoxide is 300-1000 rpm.

[0014] In one embodiment, the ratio of shellac:amino dextran:1-ethyl-(3-dimethylaminopropyl)carbodiimide:4-dimethylaminopyridine=1:1.2:1.2:0.1.

[0015] The second object of the present invention is to provide a method for preparing the above-mentioned shellac-based natural source sunscreen, which comprises: completely dissolving modified shellac in anhydrous ethanol at a concentration of 10 to 15 mg / mL, the dissolution temperature being 40 to 55° C., and the stirring rate being 300 to 1000 rpm during the dissolution; after the complete dissolution, removing a small amount of insoluble impurities by centrifugation at a speed of 6000 to 8000 rpm; completely dissolving a fat-soluble sunscreen in the ethanol solution of modified shellac at a dissolution temperature of 45 to 55° C., and the stirring rate being 300 to 1000 rpm during the dissolution; After being completely dissolved, the mixture is cooled to room temperature, and composite nanoparticles are prepared by an anti-solvent precipitation method, wherein the anti-solvent is deionized water (DI), and the emulsifier is dissolved in the anti-solvent in advance; the volume ratio of DI to solvent (anhydrous ethanol) is 10:1-5:1, and a peristaltic pump is used to drop the ethanol solution into the anti-solvent at a rate of 0.25-0.45 mL / min, and the stirring rate is 700-1000 rpm; the composite nanoparticle dispersion is rotary evaporated to remove ethanol at a temperature of 35-45°C, and finally freeze-dried to obtain a shellac-based natural source sunscreen.

[0016] The third object of the present invention is to provide the use of the above shellac-based natural sunscreen or the shellac-based natural sunscreen prepared by the above method in sunscreen cosmetics.

[0017] In one embodiment, the specific application method includes: dissolving and mixing the oil phase and the water phase respectively to prepare a cream base, and mixing and compounding with a shellac-based natural source sunscreen agent to prepare the sunscreen cosmetic.

[0018] In one embodiment, the shellac-based natural source sunscreen comprises 5-15% of the cream base.

[0019] Beneficial Effects

[0020] The present invention uses NH2-DEX to perform hydrophilic grafting modification on shellac, regulates the structure of shellac nanoparticles, and utilizes the amphiphilic properties of the modified product to prepare a shellac-based natural source sunscreen by an anti-solvent precipitation method, thereby significantly improving the ultraviolet absorption performance of pure shellac. In addition, the sunscreen cream prepared from the shellac-based natural source sunscreen has good sunscreen effect and biocompatibility, and is expected to expand the application of bio-based materials - shellac in the field of sunscreen. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 , UV-visible absorption spectrum of shellac-based natural source sunscreen (Example 1).

[0022] Figure 2 , digital photos of sunscreen (Example 2).

[0023] Figure 3 , cell compatibility of sunscreen (Example 4).

[0024] Figure 4 , Scanning Transmission Electron Microscope (STEM) images of shellac-based natural source sunscreen (Example 5).

[0025] Figure 5 , (A-C) Fourier transform infrared spectra (FTIR) and (D) UV absorption spectra of sunscreens (Examples 7-9). DETAILED DESCRIPTION

[0026] The present invention is further described below in conjunction with the accompanying drawings and examples, but the embodiments of the present invention are not limited thereto.

[0027] The modification method of the modified shellac used in the following examples is:

[0028] The shellac was completely dissolved in DMSO, and then EDC was added for activation for 30 min. Finally, DMAP and NH2-DEX were added for amidation reaction for 16 to 24 h.

[0029] It should be noted that the concentration of shellac dissolved in DMSO is 15-30 mg / mL, the dissolution temperature is 30-50°C, the stirring speed is 300-1000 rpm, and the molar ratio of raw materials is: shellac: NH2-DEX: EDC: DMAP = 1:1.2:1.2:0.1. Under the same conditions, when the concentration of shellac in DMSO, the dissolution temperature or the stirring rate changes within the above range, the shellac-based natural source sunscreen can be successfully prepared without significant effect on the material properties.

[0030] Example 1

[0031] A shellac-based natural sunscreen, the preparation method of which is as follows: the modified shellac is completely dissolved in anhydrous ethanol at a concentration of 10 mg / mL, the dissolution temperature is 40°C, and the stirring rate during dissolution is 500 rpm. After complete dissolution, a small amount of insoluble impurities are removed by centrifugation for 10 minutes, and the rotation speed is 7000 rpm. Then, sinapinic acid is completely dissolved in an ethanol solution of modified shellac at a mass ratio of 2:1 between modified shellac and sinapinic acid, the dissolution temperature is 45°C, and the stirring rate during dissolution is 500 rpm. After complete dissolution, it is cooled to room temperature, and composite nanoparticles are prepared by an antisolvent precipitation method, wherein the antisolvent is DI, Brij72 is preliminarily dissolved in DI at a concentration of 0.5 mg / mL, the volume ratio of DI to solvent (anhydrous ethanol) is 10:1, and a peristaltic pump is used to drop the ethanol solution into the antisolvent at a rate of 0.3 mL / min, and the stirring rate is 800 rpm. The composite nanoparticle dispersion was subjected to rotary evaporation to remove ethanol at a temperature of 35°C, and finally freeze-dried to obtain the shellac-based natural source sunscreen 1. The measured particle sizes are listed in Table 1.

[0032] It should be noted that when the dissolution temperature of modified shellac in anhydrous ethanol varies in the range of 40-55°C, the stirring rate during dissolution varies in the range of 300-1000rpm, the centrifugal speed varies in the range of 6000-8000rpm, the dissolution temperature of sinapinic acid in ethanol solution varies in the range of 45-55°C, the stirring rate during dissolution varies in the range of 300-1000rpm, and the rotary evaporation temperature of the composite nanoparticle dispersion varies in the range of 35-45°C, shellac-based natural source sunscreen 1 can be successfully prepared without significant effect on material properties.

[0033] The UV-3600i Plus UV-visible spectrophotometer produced by Shimadzu (Japan) Laboratory Instruments Co., Ltd. was used to scan the UV-visible absorption spectrum of the shellac-based natural sunscreen 1, and the UV-visible absorption spectrum was measured as shown in the figure below: Figure 1 Test method and conditions: The water dispersion of the shellac-based natural source sunscreen 1 was diluted to 0.5 mg / mL and subjected to UV-visible absorption spectrum scanning at room temperature.

[0034] The above shellac-based natural source sunscreen 1 is applied to the preparation of sunscreen, and the preparation method and raw material ratio are as follows and Table 2:

[0035] The oil phase and water phase components were fully dissolved at 60°C for 40 minutes, and then fully mixed at 13000 rpm for 30 minutes by a homogenizer (AN GNI AD18, Shanghai) to prepare a blank cream base. Then, 5 wt% of shellac-based natural source sunscreen 1 was added and mixed completely, and then an appropriate amount of pH stabilizer triethanolamine was added to the mixed cream to prepare sunscreen 1.

[0036] Table 2

[0037]

[0038] Properties: It is a light yellow uniform cream at room temperature.

[0039] Example 2

[0040] A shellac-based natural sunscreen, the preparation method of which is as follows: the modified shellac is completely dissolved in anhydrous ethanol at a concentration of 15 mg / mL, the dissolution temperature is 55°C, and the stirring rate during dissolution is 800 rpm. After complete dissolution, a small amount of insoluble impurities are removed by centrifugation for 10 minutes, and the rotation speed is 6500 rpm. Thereafter, ferulic acid is completely dissolved in an ethanol solution of modified shellac at a mass ratio of 10:1 between the modified shellac and the ferulic acid, the dissolution temperature is 50°C, and the stirring rate during dissolution is 800 rpm. After complete dissolution, the mixture is cooled to room temperature, and composite nanoparticles are prepared by an antisolvent precipitation method, wherein the antisolvent is DI, Tween 80 is preliminarily dissolved in DI at a concentration of 0.8 mg / mL, the volume ratio of DI to the solvent (anhydrous ethanol) is 5:1, and the ethanol solution is dripped into the antisolvent at a rate of 0.4 mL / min using a peristaltic pump, and the stirring rate is 900 rpm. The composite nanoparticle dispersion was subjected to rotary evaporation to remove ethanol at a temperature of 40°C, and finally freeze-dried to obtain the shellac-based natural source sunscreen 2. The measured particle sizes are listed in Table 1.

[0041] It should be noted that when the dissolution temperature of modified shellac in anhydrous ethanol varies in the range of 40-55°C, the stirring rate during dissolution varies in the range of 300-1000 rpm, the centrifugal speed varies in the range of 6000-8000 rpm, the dissolution temperature of ferulic acid in ethanol solution varies in the range of 45-55°C, the stirring rate during dissolution varies in the range of 300-1000 rpm, and the rotary evaporation temperature of the composite nanoparticle dispersion varies in the range of 35-45°C, shellac-based natural source sunscreen 2 can be successfully prepared without significant effect on material properties.

[0042] The above-mentioned shellac-based natural source sunscreen agent 2 is applied to the preparation of sunscreen cream. The preparation method and raw material ratio are implemented according to Example 1 to prepare sunscreen cream 2.

[0043] Properties: It is a light yellow uniform cream at room temperature. Figure 2 .

[0044] Example 3

[0045] A shellac-based natural sunscreen, the preparation method of which is as follows: the modified shellac is completely dissolved in anhydrous ethanol at a concentration of 10 mg / mL, the dissolution temperature is 50°C, and the stirring rate during dissolution is 1000 rpm. After complete dissolution, a small amount of insoluble impurities are removed by centrifugation for 10 minutes, and the rotation speed is 6000 rpm. Then, resveratrol is completely dissolved in an ethanol solution of modified shellac at a mass ratio of 2:1 of modified shellac to resveratrol, the dissolution temperature is 55°C, and the stirring rate during dissolution is 1000 rpm. After complete dissolution, it is cooled to room temperature, and composite nanoparticles are prepared by an anti-solvent precipitation method, wherein the anti-solvent is DI, sodium dodecyl sulfate is pre-dissolved in DI at a concentration of 1.2 mg / mL, the volume ratio of DI to solvent (anhydrous ethanol) is 7:1, and the ethanol solution is dripped into the anti-solvent at a rate of 0.45 mL / min using a peristaltic pump, and the stirring rate is 800 rpm. The composite nanoparticle dispersion was subjected to rotary evaporation to remove ethanol at a temperature of 45°C, and finally freeze-dried to obtain the shellac-based natural source sunscreen 3. The measured particle sizes are listed in Table 1.

[0046] It should be noted that when the dissolution temperature of modified shellac in anhydrous ethanol varies in the range of 40-55°C, the stirring rate during dissolution varies in the range of 300-1000rpm, the centrifugal speed varies in the range of 6000-8000rpm, the dissolution temperature of resveratrol in ethanol solution varies in the range of 45-55°C, the stirring rate during dissolution varies in the range of 300-1000rpm, and the rotary evaporation temperature of the composite nanoparticle dispersion varies in the range of 35-45°C, shellac-based natural source sunscreen 3 can be successfully prepared without significant effect on material properties.

[0047] The above-mentioned shellac-based natural source sunscreen agent 3 is applied to the preparation of sunscreen cream. The preparation method and raw material ratio are implemented according to Example 1 to prepare sunscreen cream 3.

[0048] Properties: It is a light yellow uniform cream at room temperature.

[0049] Example 4

[0050] A shellac-based natural sunscreen, the preparation method of which is as follows: the modified shellac is completely dissolved in anhydrous ethanol at a concentration of 15 mg / mL, the dissolution temperature is 45°C, and the stirring rate during dissolution is 300 rpm. After complete dissolution, a small amount of insoluble impurities are removed by centrifugation for 10 minutes, and the rotation speed is 7000 rpm. Then, quercetin is completely dissolved in an ethanol solution of modified shellac at a mass ratio of 7:1 to quercetin, the dissolution temperature is 50°C, and the stirring rate during dissolution is 300 rpm. After complete dissolution, it is cooled to room temperature, and composite nanoparticles are prepared by an anti-solvent precipitation method, wherein the anti-solvent is DI, Brij721 is pre-dissolved in DI at a concentration of 0.3 mg / mL, the volume ratio of DI to solvent (anhydrous ethanol) is 8:1, and the ethanol solution is dripped into the anti-solvent at a rate of 0.25 mL / min using a peristaltic pump, and the stirring rate is 1000 rpm. The composite nanoparticle dispersion was subjected to rotary evaporation to remove ethanol at a temperature of 35°C, and finally freeze-dried to obtain the shellac-based natural source sunscreen 4. The measured particle sizes are listed in Table 1.

[0051] It should be noted that when the dissolution temperature of modified shellac in anhydrous ethanol varies in the range of 40-55°C, the stirring rate during dissolution varies in the range of 300-1000rpm, the centrifugal speed varies in the range of 6000-8000rpm, the dissolution temperature of quercetin in ethanol solution varies in the range of 45-55°C, the stirring rate during dissolution varies in the range of 300-1000rpm, and the rotary evaporation temperature of the composite nanoparticle dispersion varies in the range of 35-45°C, shellac-based natural source sunscreen 4 can be successfully prepared without significant effect on material properties.

[0052] The above-mentioned shellac-based natural source sunscreen agent 4 is applied to the preparation of sunscreen cream, and the preparation method and raw material ratio are implemented according to Example 1 to prepare sunscreen cream 4.

[0053] Properties: It is a light yellow uniform cream at room temperature.

[0054] The effect of sunscreen 4 on the activity of L929 cells was analyzed by FDA cell staining method to determine its biocompatibility. 300 μg / mL of sunscreen 4 was dispersed in the culture medium of the experimental group cells, and only the culture medium was added to the control group, and cultured at 37°C, 5% CO2 for 1 day. The morphology of the cells was observed using an upright fluorescence microscope (Nikon 80i, Nikon, Japan), and fluorescence photos were taken at an excitation wavelength of 488 nm. Figure 3 As shown (the left picture is the control group, and the right picture is the experimental group). As can be seen from the figure, sunscreen 4 has no effect on the growth state of cells. The growth state of cells is good and spindle-shaped, indicating that sunscreen 4 has good biocompatibility.

[0055] Example 5

[0056] A shellac-based natural sunscreen, the preparation method of which is as follows: the modified shellac is completely dissolved in anhydrous ethanol at a concentration of 10 mg / mL, the dissolution temperature is 50°C, and the stirring rate during dissolution is 500 rpm. After complete dissolution, a small amount of insoluble impurities are removed by centrifugation for 10 minutes, and the rotation speed is 6000 rpm. Then, ethylhexyl methoxycinnamate is completely dissolved in the ethanol solution of modified shellac at a mass ratio of 5:1 between modified shellac and ethylhexyl methoxycinnamate, the dissolution temperature is 50°C, and the stirring rate during dissolution is 600 rpm. After complete dissolution, the modified shellac is cooled to room temperature, and composite nanoparticles are prepared by an anti-solvent precipitation method, wherein the anti-solvent is DI, Brij72 is preliminarily dissolved in DI at a concentration of 0.6 mg / mL, the volume ratio of DI to solvent (anhydrous ethanol) is 5:1, and the ethanol solution is dripped into the anti-solvent at a rate of 0.35 mL / min using a peristaltic pump, and the stirring rate is 800 rpm. The composite nanoparticle dispersion was subjected to rotary evaporation to remove ethanol at 40°C, and finally freeze-dried to obtain the shellac-based natural source sunscreen 5. The measured particle sizes are listed in Table 1.

[0057] It should be noted that when the dissolution temperature of modified shellac in anhydrous ethanol varies in the range of 40 to 55°C, the stirring rate during dissolution varies in the range of 300 to 1000 rpm, the centrifugal speed varies in the range of 6000 to 8000 rpm, the dissolution temperature of ethylhexyl methoxycinnamate in ethanol solution varies in the range of 45 to 55°C, the stirring rate during dissolution varies in the range of 300 to 1000 rpm, and the rotary evaporation temperature of the composite nanoparticle dispersion varies in the range of 35 to 45°C, shellac-based natural source sunscreen 5 can be successfully prepared without significant effect on material properties.

[0058] The microscopic morphology of the shellac-based natural source sunscreen 5 was observed using a scanning transmission electron microscope (STEM, Thermo Fisher Scientific Talos F200X G2, UK) at an accelerating voltage of 200 kV. Figure 4 Sample preparation method: The dispersion of shellac-based natural sunscreen 5 in water is evenly dripped onto the copper mesh, and the morphology is photographed after it is completely dried. From the STEM image, it can be seen that the shellac-based natural sunscreen 5 has a uniform and regular spherical structure, indicating that the material has been successfully prepared.

[0059] The above-mentioned shellac-based natural source sunscreen agent 5 is applied to the preparation of sunscreen cream, and the preparation method and raw material ratio are implemented according to Example 1 to prepare sunscreen cream 5.

[0060] Properties: It is a light yellow uniform cream at room temperature.

[0061] Example 6

[0062] A shellac-based natural sunscreen, the preparation method of which is as follows: the modified shellac is completely dissolved in anhydrous ethanol at a concentration of 15 mg / mL, the dissolution temperature is 55°C, and the stirring rate during dissolution is 800 rpm. After complete dissolution, a small amount of insoluble impurities are removed by centrifugation for 10 minutes, and the rotation speed is 7000 rpm. Then, homosalate is completely dissolved in an ethanol solution of modified shellac at a mass ratio of 2:1 of modified shellac to homosalate, the dissolution temperature is 55°C, and the stirring rate during dissolution is 800 rpm. After complete dissolution, the mixture is cooled to room temperature, and composite nanoparticles are prepared by an antisolvent precipitation method, wherein the antisolvent is DI, Span 80 is preliminarily dissolved in DI at a concentration of 0.9 mg / mL, the volume ratio of DI to solvent (anhydrous ethanol) is 8:1, and a peristaltic pump is used to drop the ethanol solution into the antisolvent at a rate of 0.45 mL / min, and the stirring rate is 900 rpm. The composite nanoparticle dispersion was subjected to rotary evaporation to remove ethanol at a temperature of 45°C, and finally freeze-dried to obtain the shellac-based natural source sunscreen 6. The measured particle sizes are listed in Table 1.

[0063] It should be noted that when the dissolution temperature of modified shellac in anhydrous ethanol varies in the range of 40-55°C, the stirring rate during dissolution varies in the range of 300-1000 rpm, the centrifugal speed varies in the range of 6000-8000 rpm, the dissolution temperature of homosalate in ethanol solution varies in the range of 45-55°C, the stirring rate during dissolution varies in the range of 300-1000 rpm, and the rotary evaporation temperature of the composite nanoparticle dispersion varies in the range of 35-45°C, shellac-based natural source sunscreen 6 can be successfully prepared without significant effect on material properties.

[0064] The above-mentioned shellac-based natural source sunscreen agent 6 is applied to the preparation of sunscreen cream, and the preparation method and raw material ratio are implemented according to Example 1 to prepare sunscreen cream 6.

[0065] Properties: It is a light yellow uniform cream at room temperature.

[0066] Example 7

[0067] The above shellac-based natural source sunscreen 1 is applied to the preparation of sunscreen, and the preparation method and raw material ratio are as follows and Table 3:

[0068] The oil phase and water phase components were fully dissolved at 60° C. for 40 min, respectively, and then fully mixed at 13,000 rpm for 30 min using a homogenizer (ANGNI AD18, Shanghai) to prepare a cream base 7. Then, 5 wt % of a shellac-based natural source sunscreen 1 was added to the cream base 7 and mixed thoroughly, and then an appropriate amount of a pH stabilizer, triethanolamine, was added to the mixed cream to prepare a sunscreen 7.

[0069] Table 3

[0070]

[0071] Properties: It is a light yellow uniform cream at room temperature.

[0072] Example 8

[0073] The above shellac-based natural source sunscreen 1 is applied to the preparation of sunscreen, and the preparation method and raw material ratio are as follows and Table 4:

[0074] The oil phase and water phase components were fully dissolved at 60° C. for 40 min, respectively, and then fully mixed at 13,000 rpm for 30 min using a homogenizer (ANGNI AD18, Shanghai) to prepare a cream base 8. 5 wt % of the shellac-based natural source sunscreen 1 was then added to the cream base 8 and mixed thoroughly, and then an appropriate amount of pH stabilizer triethanolamine was added to the mixed cream to prepare a sunscreen 8.

[0075] Table 4

[0076]

[0077] Properties: It is a light yellow uniform cream at room temperature.

[0078] Example 9

[0079] The above shellac-based natural sunscreen 1 is applied to the preparation of sunscreen, and the preparation method and raw material ratio are as follows:

[0080] 5 wt % of shellac-based natural sunscreen 1 was added to a commercial sunscreen with an SPF of 26 and mixed thoroughly. Then, a proper amount of pH stabilizer triethanolamine was added to the mixed cream to prepare sunscreen 9.

[0081] Properties: It is a light yellow uniform cream at room temperature.

[0082] The effects of the combination of shellac-based natural sunscreen 1 and organic small molecule sunscreen or commercial sunscreen were determined by Fourier transform infrared spectrometer (Thermo Fisher Nicolet iS50, USA) and UV-visible spectrophotometer (Shimadzu UV-3600i Plus). Figure 5 Test method and conditions: Apply sunscreens 7 to 9 to the center of a clean sample table, and use FTIR to scan the infrared spectrum to determine the hydrogen bond interactions. Scanning range: 650 cm -1 ~4000cm -1 ; Sunscreen 7 to 9 were applied at 2 mg / cm 2 The content of was smeared on a quartz glass plate and the ultraviolet absorption spectrum was scanned at room temperature. Figure 5 A~C are visible, 3360cm in the infrared spectrum -1 The peak positions on the left and right sides change, indicating the occurrence of hydrogen bonding interactions; Figure 5 D shows that the maximum absorption wavelength of the UV absorption curve is red-shifted, indicating the presence of conjugated interactions and enhanced UV absorption. The results show that shellac-based natural sunscreen 1 has complex interactions with organic small molecule sunscreens or commercial sunscreens, specifically hydrogen bonds and conjugated interactions.

[0083] Comparative Example 1

[0084] Based on Example 2, the emulsifier was removed and other preparation steps remained unchanged. The measured particle sizes are listed in Table 1.

[0085] Properties: The prepared shellac-based natural source sunscreen contains a large amount of nanoparticle aggregates in its aqueous dispersion, showing an unstable system.

[0086] Comparative Example 2

[0087] Based on Example 1, the modified shellac was replaced with pure shellac, and the other preparation steps remained unchanged.

[0088] Properties: It is a light yellow uniform cream at room temperature.

[0089] Comparative Example 3

[0090] Based on Example 9, the modified shellac was replaced by pure shellac, and the other preparation steps remained unchanged.

[0091] Properties: It is a light yellow uniform cream at room temperature.

[0092] Comparative Example 4

[0093] Based on Example 9, the fat-soluble sunscreen agent was removed and the other preparation steps remained unchanged.

[0094] Properties: It is a light yellow uniform cream at room temperature.

[0095] Particle size (nanometer) Polydispersity Index (PDI) Shellac-based sunscreen of natural origin1 139.64±1.25 0.124±0.013 Shellac-based natural sunscreen 2 108.81±2.77 0.109±0.022 Shellac-based natural sunscreen 3 171.96±4.72 0.132±0.031 Shellac-based natural sunscreen 4 221.14±3.45 0.119±0.054 Shellac-based natural sunscreen 5 135.92±3.19 0.148±0.025 Shellac-based natural sunscreen 6 218.92±2.18 0.243±0.046 Comparative Example 1 3886.81±411.89 0.333±0.011

[0096] Sun Protection Factor (SPF) Testing

[0097] The UV transmission analyzer (LabspeleUV-2000S, China) was used to test the sun protection index of the sunscreens of Examples 1, 7 to 9, and Comparative Examples 2 to 4. The specific operation method is: 2 mg / cm2 of UV-ray diffraction was evenly applied on the special PMMA plate using the same method each time. 2 After placing the sample in a dark environment for 15 minutes, 5 positions within the range of 280 to 400 nm were randomly tested on the PMMA plate, and the average value of the 5 tests was taken to obtain the sample SPF value. The results are shown in Table 5:

[0098] Table 5

[0099] SPF Sunscreen 1 15.72±0.63 Sunscreen 7 40.17±1.27 Sunscreen 8 36.48±2.32 Sunscreen 9 54.51±2.26 Comparative Example 2 12.62±1.48 Comparative Example 3 40.33±2.75 Comparative Example 4 29.35±0.98

[0100] From the SPF data of sunscreens 1, 7 to 9 listed in Table 5, it can be seen that shellac-based natural source sunscreen 1 has a certain compounding effect when mixed with other sunscreens in the form of creams. Figure 5 The data provided are consistent, and the synergistic interaction is specifically hydrogen bonding interaction and conjugation interaction. Under the action of the two, the sunscreen performance of mixed sunscreens 7 to 9 has an additional improvement. From the SPF data of sunscreen 1 and comparative example 2 (or sunscreen 9 and comparative example 3), it can be seen that the hydrophilic modification of the dextran of shellac has a positive effect on improving the sunscreen effect, which is attributed to the fact that the grafted hydrophilic dextran long chain has a certain hydrogen bonding interaction with the sunscreen matrix, making the sunscreen denser and having a better sunscreen effect. From the SPF data of comparative example 4, it can be seen that the coating of the fat-soluble sunscreen has a positive effect on improving the sunscreen effect of the sunscreen.

[0101] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A shellac-based natural sunscreen, characterized in that: The shellac-based natural sunscreen is a composite nanoparticle, comprising the following raw materials in parts by weight: 2 to 10 parts of modified shellac, 1 to 1.5 parts of fat-soluble sunscreen, and 0.01 to 1 part of emulsifier; the modified shellac is a dextran-grafted shellac product.

2. The shellac-based natural source sunscreen according to claim 1, characterized in that: The preparation method of the modified shellac is as follows: completely dissolving the shellac in dimethyl sulfoxide, adding 1-ethyl-(3-dimethylaminopropyl) carbodiimide to activate it at room temperature, and adding 4-dimethylaminopyridine and amino dextran to carry out an amidation reaction.

3. The shellac-based natural source sunscreen according to claim 1, characterized in that: The fat-soluble sunscreen is one or a combination of sinapinic acid, catechin, resveratrol, quercetin, ferulic acid, octocrylene, ethylhexyl methoxycinnamate, ethylhexyl triazone, ethylhexyl salicylate, homosalate, and avobenzone.

4. The shellac-based natural source sunscreen according to claim 1, characterized in that: The emulsifier is any one of anionic emulsifier and nonionic emulsifier or a mixture of two; Preferably, the emulsifier is at least one of sucrose ester 11, sodium lauryl sulfate, Tween 80, Span 80, Brij721, Brij72, Brij30, glyceryl stearate and sodium cetearyl sulfate.

5. The shellac-based natural source sunscreen according to claim 2, characterized in that: The concentration of the shellac dissolved in dimethyl sulfoxide is 15-30 mg / mL; the temperature when the shellac is dissolved in dimethyl sulfoxide is 30-50° C.; the stirring speed when the shellac is dissolved in dimethyl sulfoxide is 300-1000 rpm.

6. The shellac-based natural source sunscreen according to claim 2, characterized in that: The shellac: aminodextran: 1-ethyl-(3-dimethylaminopropyl)carbodiimide: 4-dimethylaminopyridine=1:1.2:1.2:0.

1.

7. The method for preparing the shellac-based natural sunscreen according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: completely dissolving the modified shellac in anhydrous ethanol at a concentration of 10 to 15 mg / mL, the dissolution temperature being 40 to 55°C, and the stirring rate being 300 to 1000 rpm during the dissolution; centrifuging for 10 minutes to remove a small amount of insoluble impurities, and the rotation speed being 6000 to 8000 rpm; completely dissolving a fat-soluble sunscreen in the ethanol solution of the modified shellac, the dissolution temperature being 45 to 55°C, and the stirring rate being 300 to 1000 rpm during the dissolution, and cooling to room temperature; dripping the ethanol solution into an anti-solvent by a peristaltic pump, the volume ratio of the anti-solvent to the ethanol solution being 10:1 to 5:1, the anti-solvent being deionized water in which an emulsifier is dissolved, the dripping rate being 0.25 to 0.45 mL / min, and the stirring rate being 700 to 1000 rpm during the dripping, to obtain a composite nanoparticle dispersion; subjecting the composite nanoparticle dispersion to rotary evaporation to remove ethanol, the temperature being 35 to 45°C, and freeze drying to obtain the shellac-based natural source sunscreen.

8. Use of the shellac-based natural sunscreen according to any one of claims 1 to 6 or the shellac-based natural sunscreen prepared by the method according to claim 7 in sunscreen cosmetics.

9. The use according to claim 8, characterized in that: The specific application method comprises: dissolving and mixing the oil phase and the water phase respectively to prepare a cream base, and mixing and compounding the base with a shellac-based natural source sunscreen agent to prepare the sunscreen cosmetic.

10. The use according to claim 9, characterized in that: Shellac-based natural source sunscreens account for 5-15% of the cream base.

Citation Information

Patent Citations

  • Particles for delivery of active ingredients, process of making and compositions thereof

    CN101500937A

  • Shellac based skin care lotion

    CN106132395A

  • Zein-based nanometer sunscreen agent, and preparation method and application thereof

    CN108815007A

  • Preparation method of gelatin-based sunscreen emulsion

    CN109758383A

  • Broad-spectrum sun-blocking composite nanoparticle and preparation method thereof

    CN110215411A